A Study on the Motivation of Mexican High School Students to Attend High School - Rosa del Carmen Flores Macías; Josefina Gómez Bastida (Universidad Autónoma de Baja California, 2010)
Motivation studies have focused on three aspects that are important for their educational implications: relevant variables for assessing motivation to attend school; motivational differences between students with different academic performance, and changes in motivation as they advance in school. Considering these aspects, the present study was developed with these objectives: to develop, and to set up the validity and reliability of a psychometric instrument for investigating how people perceive different motivational variables regarding various school activities typical of the Mexican junior high school; and to find out whether there is a relationship between motivational variables and academic achievement, grade level and gender. The results indicate that academic performance is related to the way motivation is perceived, that students change their perception of motivation during their school life, and that boys and girls differ concerning this only in some respects.